2018
DOI: 10.4103/abr.abr_164_17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Pattern and Spectrum of Multiple-drug-resistant Enterobacteriaceae in Iranian Hospitalized Patients with Cancer

Abstract: Background:Nosocomial infections are one of the most leading causes of morbidity and mortality in patients with cancer. The emergence of multiple-drug-resistant (MDR) strains of Gram-negative bacteria causing nosocomial infection has become a serious concern in cancer patients. Therefore, the present study aimed to determine the spectrum and antibiotic resistance pattern of Gram-negative bacteria related nosocomial infections among Iranian cancer patients.Materials and Methods:This descriptive cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…This finding was in agreement with the study conducted in Egypt (30%) and India (40%) [ 19 , 20 ]. However, this finding was lower (60.6%) than the study documented in Iranian cancer patients [ 21 ] and higher than (21.2%) the study recorded in Gondar [ 14 ]. The second frequently isolated gram-negative bacteria were Klebsiella pneumonia (22.2%) which is in lined with the study documented by Ashour and El-Sharif [ 19 ].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding was in agreement with the study conducted in Egypt (30%) and India (40%) [ 19 , 20 ]. However, this finding was lower (60.6%) than the study documented in Iranian cancer patients [ 21 ] and higher than (21.2%) the study recorded in Gondar [ 14 ]. The second frequently isolated gram-negative bacteria were Klebsiella pneumonia (22.2%) which is in lined with the study documented by Ashour and El-Sharif [ 19 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Intriguingly, we did not identify any gram positive bacteria and Pseudomonas aeruginosa from gram negative bacteria in our study participants even if these uropathogen were a commonly isolated as etiologic agent of UTI [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an expected outcome due to the worldwide existence and prevalence of multidrug-resistant clones [48][49][50]. Similarly, a study in Iranian hospitalized patients with cancer showed significant spreading of MDR gram-negative bacteria, which may raise the problem of healthcare-associated infections in cancer patients [51,52].…”
Section: Antibiotic Nonsusceptibilitymentioning
confidence: 99%
“…There is increasing evidence from different parts of the world of the high prevalence of antimicrobial resistance (AMR) in cancer patients [ 1 , 2 , 3 , 4 , 5 ]. Patients with cancers are immunosuppressed and therefore at a high risk of serious opportunistic infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%